Solid waste regenerated water permeable brick and preparation method thereof
By using functional aggregates formed by blast furnace slag, sagite powder and fosperidite powder, and combining with other materials, solid waste recycled permeable bricks with high strength are prepared, which solves the problem of low strength of existing permeable bricks and achieves efficient use of materials and environmental protection.
Patent Information
- Application Number
- CN202510385497.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-29
AI Technical Summary
The existing permeable bricks have low strength, and the commonly used cemented cementitious materials are incompletely hydrated in low temperature or dry environments, which affects early strength growth.
Functional aggregates formed by blast furnace slag, sagite powder and magnesium sterilite powder are used to combine coal gangue, fly ash, cement, aluminum powder paste, water reducing agent and pore-making agent, and a solid waste recycled permeable brick with uniform pores and high strength are prepared through ball milling, stirring, sintering and other steps.
The split tensile strength of solid waste recycled permeable bricks is significantly improved, the effective utilization of solid waste materials is achieved, the pollution to the environment is reduced, and the permeability is improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of permeable bricks, and in particular to a solid waste recycled permeable brick and a preparation method thereof. Background Art
[0002] Permeable bricks are porous products that form pavements that can effectively absorb rainwater and achieve water penetration from the surface to the ground. They can not only effectively penetrate and purify water, but also release and store water, and are widely used. For example, when they are laid on sidewalks and pedestrian streets, rainwater can quickly penetrate into the ground; when they are used in urban leisure squares, commercial squares and other places, they can not only drain water, but also adjust the local temperature and humidity of the square and improve the square environment.
[0003] At present, permeable bricks are mostly made of common cementitious materials such as cement and natural aggregates such as river sand and quartz sand, and the use of solid waste materials is relatively small. In addition, the hydration of commonly used cement cementitious materials is greatly affected by the ambient temperature and humidity. In low temperature or dry environment, the hydration reaction is incomplete, resulting in slow growth of the early strength of permeable bricks; natural aggregates are also unevenly distributed. These factors will affect the strength of permeable bricks.
[0004] Therefore, it is of great significance to develop a permeable brick made of solid waste as raw materials. It can not only realize the reuse of solid waste materials, but also improve the strength of permeable bricks, which plays an important role in improving the performance of permeable bricks, promoting the resource utilization of solid waste and achieving environmental sustainable development. Summary of the invention
[0005] The present invention provides a solid waste recycled permeable brick and a preparation method thereof, which solves the problem of low strength of the permeable brick in the related art.
[0006] The technical solution of the present invention is as follows: The present invention provides a solid waste recycled permeable brick, comprising the following components in parts by weight: 10-20 parts of coal gangue, 10-16 parts of fly ash, 20-30 parts of cement, 44-65 parts of functional aggregate, 2-4 parts of aluminum paste, 140-150 parts of water, 2-4 parts of water reducer, 5-8 parts of pore-forming agent; The raw materials of the functional aggregate include blast furnace slag, palygorskite powder and forsterite powder in a weight ratio of 20:1:1-19.
[0007] As a further technical solution, the weight ratio of the blast furnace slag, palygorskite powder and forsterite powder is 20:1:4~9.
[0008] When the weight ratio of blast furnace slag, palygorskite powder and forsterite powder is 20:1:4~9, the splitting tensile strength of the solid waste recycled permeable brick can be 6.8~6.9MPa, which further improves the strength of the solid waste recycled permeable brick; when the weight ratio of blast furnace slag, palygorskite powder and forsterite powder is outside the range of 20:1:4~9, the strength of the solid waste recycled permeable brick is slightly worse.
[0009] As a further technical solution, the preparation method of the functional aggregate comprises the following steps: A1, mixing the blast furnace slag and forsterite powder uniformly, and ball milling to obtain a mixture; A2. Add palygorskite powder and water to the mixture, stir, granulate, sinter, and cool to obtain functional aggregate.
[0010] As a further technical solution, in step A1, during the ball milling treatment, the ball milling speed is 150-200 r / min, and the ball milling time is 1-2 h; In step A2, the stirring is divided into primary stirring and secondary stirring. During the primary stirring, the speed is 300-500 r / min and the time is 50-80 min; during the secondary stirring, the speed is 800-900 r / min and the time is 30-60 min; In step A2, the sintering is divided into primary sintering and secondary sintering. During the primary sintering, the temperature is 715-820° C. and the time is 20-30 seconds; during the secondary sintering, the temperature is 960-980° C. and the time is 10-15 seconds.
[0011] In the present invention, in the preparation process of the functional aggregate, the blast furnace slag and the forsterite powder are firstly ball-milled at a suitable ball-milling speed, so that the blast furnace slag and the forsterite powder particles are refined, and the blast furnace slag and the forsterite powder are mixed more evenly, and a higher reaction activity is provided for the subsequent sintering process, so as to better combine with the palygorskite powder; In the process of combining with palygorskite powder, first stir at 300-500r / min for 50-80min. The purpose of long-time stirring at low speed is to make palygorskite powder evenly dispersed in the system and give full play to the adsorption and combination effect with blast furnace slag and forsterite powder. Then stir at 800-900r / min for 30-60min. The purpose of increasing the stirring speed and shortening the stirring time is to further adjust the uniform density of the three and lay the foundation for subsequent sintering. During the sintering process, within the temperature range of 715~820℃, the evaporation of water in the system can form a porous structure in the aggregate during the sintering process, which is convenient for further homogenization of the pores under the action of aluminum powder paste during the preparation of permeable bricks; and sintering at 960~980℃ for a shorter time can form a stable aggregate structure and chemical bonds, thereby improving the strength of the functional aggregate.
[0012] As a further technical solution, the water reducer is one or two of lignin sulfonate and naphthalene-based water reducer; The pore-forming agent is one or both of polyvinyl alcohol and starch.
[0013] As a further technical solution, the functional aggregate is a bisphenol A epoxy acrylate composite functional aggregate, and the raw materials of the bisphenol A epoxy acrylate composite functional aggregate include functional aggregate and bisphenol A epoxy acrylate in a weight ratio of 30:1-4.
[0014] As a further technical solution, the weight ratio of the functional aggregate to bisphenol A epoxy acrylate is 30:2~3.
[0015] In the present invention, bisphenol A epoxy acrylate is used to perform composite treatment on the functional aggregate formed by blast furnace slag, forsterite powder and palygorskite powder, so as to improve the water permeability of solid waste recycled permeable bricks. The reason may be that bisphenol A epoxy acrylate improves the interface bonding between the functional aggregate and the other components in the solid waste recycled permeable bricks, and during the forming process of the solid waste recycled permeable bricks, the tightness between the functional aggregate and other components can be adjusted, and the components can be formed to a certain extent. The interconnected pore structure, thereby improving the water permeability of the solid waste recycled permeable bricks, and when the weight ratio of the functional aggregate to bisphenol A epoxy acrylate is 30:2~3, the water permeability of the solid waste recycled permeable bricks can be made better.
[0016] As a further technical solution, the method for preparing the bisphenol A epoxy acrylate composite functional aggregate comprises the following steps: B1, mixing the blast furnace slag and forsterite powder evenly, and ball milling to obtain a mixture; B2, adding palygorskite powder and water to the mixture, stirring, granulating, sintering, cooling, and obtaining a functional aggregate; B3, dispersing the bisphenol A epoxy acrylate in ethyl acetate, adding functional aggregate and benzoin dimethyl ether, mixing evenly, irradiating with ultraviolet light, and drying to obtain bisphenol A epoxy acrylate composite functional aggregate.
[0017] As a further technical solution, the weight ratio of the functional aggregate to ethyl acetate is 1:0.4~0.6.
[0018] As a further technical solution, the weight ratio of bisphenol A epoxy acrylate to benzoin dimethyl ether is 20:1.
[0019] As a further technical solution, the mixing is carried out by stirring; during the stirring, the temperature is 50-60° C., the speed is 400-600 r / min, and the time is 4-6 hours.
[0020] As a further technical solution, the ultraviolet light irradiation time is 2 to 5 minutes.
[0021] The present invention also proposes a method for preparing a solid waste recycled permeable brick, comprising the following steps: S1. Evenly mix the coal gangue, fly ash, cement, functional aggregate and 60% to 70% by weight of water to obtain mixed slurry I; S2, adding the remaining weight of water, water reducing agent and pore forming agent to the mixed slurry I, mixing evenly to obtain mixed slurry II, adding aluminum powder paste to the mixed slurry II, stirring to obtain mixed slurry III; S3, pressing the mixed slurry III into shape, and curing it to obtain solid waste recycled permeable bricks.
[0022] As a further technical solution, in step S1 and step S2, the mixing is carried out by stirring, the stirring speed is independently 300-400 r / min, and the stirring time is independently 13-25 min.
[0023] As a further technical solution, in step S3, the pressure during the pressing molding is 12-18 MPa.
[0024] As a further technical solution, in step S3, during the curing, the temperature is 24-28°C and the curing time is 28 days.
[0025] The working principle and beneficial effects of the present invention are: 1. In the present invention, a functional aggregate formed by blast furnace slag, palygorskite powder and forsterite powder is used as the main base material. Under the effective action of coal gangue, fly ash, cement, aluminum paste, water reducer and pore-forming agent, a permeable brick with uniform pores and high strength is obtained. Among them, solid waste materials such as coal gangue, fly ash and blast furnace slag are used to replace traditional natural aggregates such as river sand and quartz sand, which realizes the effective utilization of solid waste materials to a certain extent and reduces the pollution to the environment caused by the discharge of solid waste materials such as slag.
[0026] 2. In the present invention, the functional aggregate formed by blast furnace slag, palygorskite powder and forsterite powder is added to the components of the permeable brick, so that the permeable brick has good bearing capacity. The functional aggregate formed by the composite treatment of blast furnace slag, palygorskite powder and forsterite powder has a uniform and stable structure, which can play a good supporting role in the permeable brick, thereby improving the strength of the permeable brick. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the following embodiments and comparative examples, the average particle size of blast furnace slag is 45 μm; the average particle size of forsterite powder is 48 μm; the average particle size of palygorskite powder is 10 μm; the average particle size of coal gangue is 45 μm; the average particle size of fly ash is 25 μm; cement is ordinary Portland cement, model P·O 42.5; calcium lignin sulfonate is selected as a water reducer; polyvinyl alcohol is selected as a pore-forming agent, model PVA 1788; the model of aluminum powder paste is GLS-65; and the model of bisphenol A epoxy acrylate is YC3381S.
[0029] Example 1 The preparation method of functional aggregate comprises the following steps: A1. Mix 40 parts of blast furnace slag and 2 parts of forsterite powder, and ball mill them at 150 r / min for 2 h to obtain a mixture; A2. Add 2 parts of palygorskite powder and 100 parts of water to the above mixture, stir at 300 r / min for 80 min, stir at 800 r / min for 60 min, granulate, sinter at 715°C for 30 s, heat to 960°C at a heating rate of 50°C / min, sinter at 960°C for 15 s, and cool to obtain functional aggregate; A method for preparing solid waste recycled permeable bricks comprises the following steps: S1. 10 parts of coal gangue, 10 parts of fly ash, 20 parts of cement, 44 parts of the above functional aggregate and 84 parts of water were stirred at 300 r / min for 25 min to obtain mixed slurry I; S2. Add 56 parts of water, 2 parts of calcium lignin sulfonate and 5 parts of polyvinyl alcohol to the mixed slurry I, stir at 300 r / min for 25 minutes to mix evenly, to obtain mixed slurry II, add 2 parts of aluminum powder paste to the mixed slurry II, stir to obtain mixed slurry III; S3. Press the mixed slurry III into a mold at a pressure of 12 MPa, demould, and cure at 24°C for 28 days to obtain solid waste recycled permeable bricks.
[0030] Example 2 The preparation method of functional aggregate comprises the following steps: A1. Mix 40 parts of blast furnace slag and 6 parts of forsterite powder, and ball mill them at 180 r / min for 1.5 h to obtain a mixture; A2. Add 2 parts of palygorskite powder and 100 parts of water to the above mixture, stir at 400 r / min for 65 min, stir at 850 r / min for 45 min, granulate, sinter at 775°C for 25 s, heat to 970°C at a heating rate of 50°C / min, sinter at 970°C for 15 s, and cool to obtain functional aggregate; A method for preparing solid waste recycled permeable bricks comprises the following steps: S1. 15 parts of coal gangue, 13 parts of fly ash, 25 parts of cement, 60 parts of the above functional aggregate and 94.9 parts of water were stirred at 350 r / min for 18 min to obtain mixed slurry I; S2, adding 51.1 parts of water, 3 parts of calcium lignin sulfonate and 6 parts of polyvinyl alcohol to the mixed slurry I, stirring at 350 r / min for 18 minutes to mix evenly, to obtain mixed slurry II, adding 3 parts of aluminum powder paste to the mixed slurry II, stirring to obtain mixed slurry III; S3. Press the mixed slurry III into a mold at a pressure of 16 MPa, demould, and cure at 26°C for 28 days to obtain solid waste recycled permeable bricks.
[0031] Example 3 The preparation method of functional aggregate comprises the following steps: A1. 32.5 parts of blast furnace slag and 30.875 parts of forsterite powder were mixed uniformly, and ball-milled at 200 r / min for 1 h to obtain a mixture; A2. Add 1.625 parts of palygorskite powder and 100 parts of water to the above mixture, stir at 500 r / min for 50 min, stir at 900 r / min for 30 min, granulate, sinter at 820° C. for 20 s, heat to 980° C. at a heating rate of 50° C. / min, sinter at 980° C. for 10 s, and cool to obtain a functional aggregate; A method for preparing solid waste recycled permeable bricks comprises the following steps: S1. 20 parts of coal gangue, 16 parts of fly ash, 30 parts of cement, 65 parts of the above functional aggregate and 105 parts of water were stirred at 400 r / min for 13 minutes to obtain mixed slurry I; S2. Add 45 parts of water, 4 parts of calcium lignin sulfonate and 8 parts of polyvinyl alcohol to the mixed slurry I, stir at 400 r / min for 13 minutes to mix evenly, to obtain mixed slurry II, add 4 parts of aluminum powder paste to the mixed slurry II, stir to obtain mixed slurry III; S3. Press the mixed slurry III into shape in a mold at a pressure of 18 MPa, demould, and cure at 28°C for 28 days to obtain solid waste recycled permeable bricks.
[0032] Example 4 The only difference between this embodiment and embodiment 2 is that in this embodiment, during the preparation of the functional aggregate, 6 parts of forsterite powder are replaced with 20 parts of forsterite powder.
[0033] Example 5 The only difference between this embodiment and embodiment 2 is that in this embodiment, during the preparation of the functional aggregate, 6 parts of forsterite powder are replaced by 8 parts of forsterite powder.
[0034] Example 6 The only difference between this embodiment and embodiment 2 is that in this embodiment, during the preparation of the functional aggregate, 6 parts of forsterite powder are replaced with 18 parts of forsterite powder.
[0035] Example 7 The difference between this embodiment and embodiment 6 is that in this embodiment, the functional aggregate is a bisphenol A epoxy acrylate composite functional aggregate, and its preparation method includes the following steps: B1, 40 parts of blast furnace slag and 18 parts of forsterite powder were mixed evenly, and ball milled at 180 r / min for 1.5 h to obtain a mixture; B2. Add 2 parts of palygorskite powder and 100 parts of water to the above mixture, stir at 400 r / min for 65 min, stir at 850 r / min for 45 min, granulate, sinter at 775°C for 25 s, heat to 970°C at a heating rate of 50°C / min, sinter at 970°C for 15 s, and cool to obtain functional aggregate; B3, after dispersing 2 parts of bisphenol A epoxy acrylate in 30 parts of ethyl acetate, add 60 parts of the above functional aggregate and 0.1 parts of benzoin dimethyl ether, stir at 50°C at a stirring speed of 500r / min for 5h to mix evenly, irradiate with ultraviolet light for 3min, and dry to obtain bisphenol A epoxy acrylate composite functional aggregate; A method for preparing solid waste recycled permeable bricks comprises the following steps: S1, 15 parts of coal gangue, 13 parts of fly ash, 25 parts of cement, 60 parts of the above-mentioned bisphenol A epoxy acrylate composite functional aggregate and 94.9 parts of water, stirred at 350r / min for 18min to mix evenly, to obtain mixed slurry I; S2, adding 51.1 parts of water, 3 parts of calcium lignin sulfonate and 6 parts of polyvinyl alcohol to the mixed slurry I, stirring at 350 r / min for 18 minutes to mix evenly, to obtain mixed slurry II, adding 3 parts of aluminum powder paste to the mixed slurry II, stirring to obtain mixed slurry III; S3. Press the mixed slurry III into a mold at a pressure of 16 MPa, demould, and cure at 26°C for 28 days to obtain solid waste recycled permeable bricks.
[0036] Example 8 The only difference between this embodiment and embodiment 7 is that, in this embodiment, 2 parts of bisphenol A epoxy acrylate are replaced by 8 parts of bisphenol A epoxy acrylate.
[0037] Example 9 The only difference between this embodiment and embodiment 7 is that in this embodiment, 2 parts of bisphenol A epoxy acrylate are replaced by 4 parts of bisphenol A epoxy acrylate.
[0038] Example 10 The only difference between this embodiment and embodiment 7 is that, in this embodiment, 2 parts of bisphenol A epoxy acrylate are replaced by 6 parts of bisphenol A epoxy acrylate.
[0039] Embodiment 11 A method for preparing solid waste recycled permeable bricks comprises the following steps: S1, 10 parts of coal gangue, 10 parts of fly ash, 20 parts of cement, 40 parts of blast furnace slag, 2 parts of forsterite powder, 2 parts of palygorskite powder and 84 parts of water, stirred at 300 r / min for 25 min to mix evenly, to obtain mixed slurry I; S2. Add 56 parts of water, 2 parts of calcium lignin sulfonate and 5 parts of polyvinyl alcohol to the mixed slurry I, stir at 300 r / min for 25 minutes to mix evenly, to obtain mixed slurry II, add 2 parts of aluminum powder paste to the mixed slurry II, stir to obtain mixed slurry III; S3. Press the mixed slurry III into a mold at a pressure of 12 MPa, demould, and cure at 24°C for 28 days to obtain solid waste recycled permeable bricks.
[0040] Comparative Example 1 The only difference between this comparative example and Example 1 is that in this comparative example, the palygorskite powder is replaced by an equal amount of zeolite.
[0041] Comparative Example 2 The only difference between this comparative example and Example 1 is that in this comparative example, the forsterite powder is replaced by an equal amount of fayalite powder.
[0042] Comparative Example 3 The only difference between this comparative example and Example 1 is that in this comparative example, blast furnace slag is replaced by an equal amount of steel slag.
[0043] Comparative Example 4 The only difference between this comparative example and Example 1 is that in this comparative example, the palygorskite powder and the forsterite powder are replaced by an equal amount of blast furnace slag.
[0044] Comparative Example 5 The only difference between this comparative example and Example 1 is that in this comparative example, blast furnace slag and palygorskite powder are replaced by an equal amount of forsterite powder.
[0045] Comparative Example 6 The only difference between this comparative example and Example 1 is that in this comparative example, blast furnace slag and forsterite powder are replaced by an equal amount of palygorskite powder.
[0046] Comparative Example 7 The only difference between this comparative example and Example 1 is that in this comparative example, no functional aggregate is added.
[0047] Experimental Example 1 The solid waste recycled permeable bricks prepared in Examples 1 to 6, Example 11 and Comparative Examples 1 to 7 were subjected to splitting tensile strength test according to the method in GB / T25993-2023 "Permeable Pavement Bricks and Permeable Road Panels", wherein the load was uniformly applied at a loading rate of 0.05 MPa / s until the specimen broke. The result is the average value of 5 specimens. The test results are shown in Table 1: Table 1 Splitting tensile strength test results of Examples 1 to 6, Example 11 and Comparative Examples 1 to 7
[0048] Compared with Comparative Examples 1 to 7, the splitting tensile strength of the solid waste recycled permeable bricks prepared in Examples 1 to 6 is improved, indicating that when the functional aggregate includes blast furnace slag, palygorskite powder and forsterite powder, the blast furnace slag, palygorskite powder and forsterite powder have a synergistic effect and can significantly improve the strength of the solid waste recycled permeable bricks.
[0049] Experimental Example 2 The solid waste recycled permeable bricks prepared in Examples 6 to 10 were tested for water permeability according to the method in GB / T 25993-2023 "Permeable Pavement Bricks and Permeable Road Panels", wherein the test results are the average values of the three samples, and the test results are shown in Table 2: Table 2 Water permeability test results of Examples 6 to 10
[0050] Compared with Example 6, the water permeability coefficient of the solid waste recycled permeable bricks prepared in Examples 7 to 10 is improved, indicating that the composite treatment of functional aggregates with bisphenol A epoxy acrylate can improve the water permeability of solid waste recycled permeable bricks.
[0051] Experimental Example 3 The solid waste recycled permeable bricks prepared in Examples 1 to 3 were tested for frost resistance according to the method in GB / T 25993-2023 "Permeable Pavement Bricks and Permeable Road Panels", wherein the freeze-thaw cycle was 150 times, and the average strength loss rate of the five specimens after 150 freeze-thaw cycles was tested, and the average strength loss rate (%) = (average compressive strength of five non-freeze-thaw compressive strength specimens - average compressive strength of five freeze-thaw compressive strength specimens) / average compressive strength of five non-freeze-thaw compressive strength specimens × 100%. The test results are shown in Table 3: Table 3 Antifreeze performance test results of Examples 1 to 3
[0052] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A solid waste recycled permeable brick, characterized in that: The composition comprises the following components in parts by weight: 10-20 parts of coal gangue, 10-16 parts of fly ash, 20-30 parts of cement, 44-65 parts of functional aggregate, 2-4 parts of aluminum paste, 140-150 parts of water, 2-4 parts of water reducer, 5-8 parts of pore-forming agent; The raw materials of the functional aggregate include blast furnace slag, palygorskite powder and forsterite powder in a weight ratio of 20:1:1-19.
2. The solid waste recycled permeable brick according to claim 1, characterized in that: The weight ratio of the blast furnace slag, palygorskite powder and forsterite powder is 20:1:4-9.
3. The solid waste recycled permeable brick according to claim 1, characterized in that: The preparation method of the functional aggregate comprises the following steps: A1, mixing the blast furnace slag and forsterite powder uniformly, and ball milling to obtain a mixture; A2. Adding palygorskite powder and water to the mixture, stirring, granulating, sintering, and cooling to obtain functional aggregate.
4. The solid waste recycled permeable brick according to claim 3, characterized in that: In step A1, during the ball milling treatment, the ball milling speed is 150-200 r / min, and the ball milling time is 1-2 h.
5. The solid waste recycled permeable brick according to claim 3, characterized in that: In step A2, the stirring is divided into primary stirring and secondary stirring. During the primary stirring, the speed is 300-500 r / min and the time is 50-80 min; during the secondary stirring, the speed is 800-900 r / min and the time is 30-60 min; In step A2, the sintering is divided into primary sintering and secondary sintering. During the primary sintering, the temperature is 715-820° C. and the time is 20-30 seconds; during the secondary sintering, the temperature is 960-980° C. and the time is 10-15 seconds.
6. The solid waste recycled permeable brick according to claim 1, characterized in that: The water reducer is one or both of lignin sulfonate and naphthalene-based water reducer; The pore-forming agent is one or both of polyvinyl alcohol and starch.
7. The solid waste recycled permeable brick according to claim 1, characterized in that: The functional aggregate is a bisphenol A epoxy acrylate composite functional aggregate, and the raw materials of the bisphenol A epoxy acrylate composite functional aggregate include functional aggregate and bisphenol A epoxy acrylate in a weight ratio of 30:1-4.
8. The solid waste recycled permeable brick according to claim 7, characterized in that: The weight ratio of the functional aggregate to bisphenol A epoxy acrylate is 30:2-3.
9. The method for preparing a solid waste recycled permeable brick according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Evenly mix the coal gangue, fly ash, cement, functional aggregate and 60% to 70% by weight of water to obtain mixed slurry I; S2, adding the remaining weight of water, water reducing agent and pore forming agent to the mixed slurry I, mixing evenly to obtain mixed slurry II, adding aluminum powder paste to the mixed slurry II, stirring to obtain mixed slurry III; S3, pressing the mixed slurry III into shape, and curing it to obtain solid waste recycled permeable bricks.
10. The method for preparing a solid waste recycled permeable brick according to claim 9, characterized in that: In step S3, during the pressing process, the pressure is 12-18 MPa.
Citation Information
Patent Citations
Preformed material for post-tensioned prestressing pipeline vacuum grouting or mudjacking and preparation method thereof
CN101602589A
High-shock resistance aerated building block and making method thereof
CN105272133A
Recycled aggregate water-permeable brick and production method thereof
CN110407533A
Ecological water permeable brick and preparation method thereof
CN114044655A
Cited By
Coal gangue roadbed material and preparation method thereof
CN120903894A